Multiple recurrent cerebral hydatidosis: A case report with review of literature - Nikhita, P; Vani, HN; Dattatreya, P; Nijaguna, N (Asian Journal of Medical Sciences, 2015)
Echinococcisis is an emerging zoonotic parasitic disease worldwide and is a significant health burden among developing nations. Cystic hydatidosis is more commonly found in lungs and liver but rarely cerebral involvement can occur. Multiple hydatid cysts of brain are uncommon and may be wither primary or secondary. Hydatid cyst shoud be considered as a differential diagnosis for cystic lesions of the brain. Here we are reporting a 8 year old boy with multiple cerebral hydatid cysts recurring within three months after surgical rupture of a primary large cerebral hydatid cyst. Asian Journal of Medical Sciences Vol.7(1) 2015 105-107